Corporate Waqf in Indonesia: Development, Governance Challenges, and Sustainable Prospects - Sulistiani, Siska Lis; Gumilar, Agi Sukma (Fakultas Ekonomi dan Bisnis Islam _ IAIN Sultan Amai Gorontalo, 2025)
This study aims to examine the development, governance, and challenges of corporate waqf in Indonesia, with a particular focus on regulatory frameworks, digital innovation, and its contribution to sustainable development. Employing a qualitative descriptive approach, this research is based on a systematic literature review and secondary data analysis from academic journals, government reports, and institutional publications. The findings reveal that corporate waqf in Indonesia has demonstrated significant growth, particularly through CWLS, which recorded an increase from Rp 5 billion in 2020 to Rp 88 billion in 2023. Corporate waqf has also shown measurable social returns, with evidence suggesting that every Rp 1 billion invested can generate Rp 2.3 billion in social value annually. However, the expansion of corporate waqf remains constrained by regulatory gaps, fragmented digital platforms, and limited managerial capacity among waqf administrators. The study concludes that corporate waqf has strong potential to become a strategic instrument for inclusive and sustainable development in Indonesia. To realize this potential, stakeholders must strengthen derivative regulations, standardize governance frameworks, and integrate waqf into corporate Environmental, Social, and Governance (ESG) strategies. These steps will not only enhance transparency and accountability but also ensure that corporate waqf evolves from sporadic philanthropic initiatives into a sustainable mechanism of Islamic social finance capable of contributing to national and global development goals.